Effectiveness of Using Learning Media to Improve Student Learning Outcomes at SMA Negeri 10 Wajo - Dewi, Asmila; Yany, Muhamad; Hamka, Hamka (JUPE : Jurnal Pendidikan Mandala, 2024)
This thesis describes several things related to the influence of the use of learning media on learning outcomes, especially for students at SMA Negeri 10 Wajo.The method used in reviewing the research in this thesis is ex post facto with a quantitative approach. The data collection techniques used in this research are: observation, questionnaires and documentation.Research based on initial observations shows that the use of appropriate learning media can influence student learning outcomes.The results of this research indicate that the use of learning media has a significant positive effect on student learning outcomes. Students who study with audiovisual learning media tend to achieve better learning outcomes compared to those who do not use this media.